The Prevalence of Virulence Genes and Virulotypes of Escherichia coli Strains Isolated from Hospital Wastewaters in Tehran, Iran - Reza RANJBAR; Omid FARAHANI (Tehran University of Medical Sciences, 2018)
Background: Due to the widespread different pathogenic strains, Escherichia coli lead many severe to normal diseases worldwide. Finding the relation of clones with genomic content and clinical features is a key point to recognize the high potential-invasive strains. Specific virulence factors include adhesions, invasions, toxins, and capsule are the main determinants of pathogenic factors of E. coli strains. Methods: From Jun 2014 to Jun ‎‎2016, E. coli isolates recovered using standard bacteriological methods from wastewater sources in different hospitals in Tehran, Iran, were monitored to recognize the virulence genes by polymerase chain reaction (PCR) assay. Results: The high and low presences of virulence factors were fimH, 76% and afa, 13%, respectively. Conclusion: The results indicated the potential pathogenicity of E. coli strains circulating in hospital wastewaters in Tehran, Iran.